Arabic Language Learning Through Multicultural Approach in Indonesia and Malaysia: (A Comparative Descriptive Analysis) - sulistyaningsih; Syamsiyah, Dailatus (An Naba, 2025)
This study investigates the implementation of Arabic language education through a multicultural approach in Indonesia and Malaysia. It aims to compare teaching strategies, curriculum content, and the socio-cultural context that influence Arabic learning in both countries. As Arabic is not only a religious language but also a cultural bridge, its teaching can foster tolerance and respect for diversity. Using a qualitative-comparative method, data were collected through interviews, observations, and document analysis from Islamic educational institutions in both countries. The findings show that both nations share the goal of promoting inclusive values through Arabic education, though their approaches differ. Indonesia is moving toward contextual and participatory teaching, while Malaysia uses a structured system combining separation and integration models. Challenges include limited teacher training, varied student backgrounds, and lack of culturally responsive materials. Despite this, Arabic education has proven effective in shaping students’ awareness of multicultural values when designed inclusively. This research provides insights for educators and policymakers to enhance Arabic curricula as a medium for building intercultural understanding and social harmony.